The Cox Proportional Hazard Model on Life Insurance Premium Payments Analysis - Nor Amalliyah (Department of Mathematics, Hasanuddin University, 2024)
Insurance premiums are a sum of money that must be paid by participants of life insurance programs to insurance companies to compensate for losses suffered by participants. The amount of the premium must be in accordance with the sum insured to be received, so that the insurance company has enough money to replace the losses suffered by its customers. In determining the premiums also should not be too large, because it can burden the insurance program customers. Therefore it is necessary to do an analysis to find out the factors (gender, age, amount of coverage, occupation, method of payment of premiums, amount of premium, and type of insurance product) that affect the term of payment ability by the customer. The analysis conducted is using the Cox Proportional Hazard Model. The results obtained in this study are factors that have a significant effect on the period of ability to pay premiums, namely the amount of sum insured, profession and types of insurance product